Community pharmacist-administered seasonal influenza vaccination: a national customer survey - Dominik Stämpfli (Journal of Pharmaceutical Policy and Practice, 2020)
Abstract Background In Switzerland, the influenza vaccination is recommended for high-risk groups and people who have contact with high-risk groups. Since 2015, Swiss pharmacists are allowed to vaccinate healthy adults after acquiring a certificate of competence for vaccination and blood sampling techniques. We aimed to assess customers of the seasonal influenza vaccination in pharmacies in regard to their satisfaction, motivation, and reasons. Methods Swiss pharmacies collected survey data during a period of 12 weeks from mid-October 2019 to mid-January 2020. Each participating pharmacy was sent 20 questionnaires to be handed out to vaccinated customers. The questionnaire was available in German and French and subdivided into four sections: demographic information, satisfaction, reasons for getting the vaccination, and reasons for choosing a pharmacy as a place of vaccination. We tested for statistical differences in answer tendencies across strata on questionnaire language, age groups, and levels of education. Results Of the 1600 surveys sent, 80 pharmacies sent back 656 completed questionnaires (return rate, 41%). Main age bracket was 65–74 years (26.2%), followed by 55–64 years (24.7%), with an equal distribution of reported sex (female, 49.5%). Of the respondents, 99% would have recommended the service and 88.5% felt very comfortable being vaccinated by a pharmacist. Satisfaction included injection technique, used facilities, preparatory discussions, and pricing of the service. Easy scheduling was a main motivation for choosing a pharmacy as the vaccination provider. We identified minor differences in answer tendencies across questionnaire language and age groups, but not across levels of education. Conclusion Customer satisfaction with community pharmacist-administered seasonal influenza vaccinations is high in Switzerland.